Biologic treatments in Behcet's disease - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (AVES, 2021)
Behcet's disease (BD) significantly increases morbidity and mortality, especially in young men. While vascular involvement is the most frequent cause of mortality, ocular involvement, which can cause visual loss, is the most important cause of morbidity in BD. Immunosuppressive treatment is the mainstay for major organ involvement. However, despite optimal immunosuppressive treatment, relapses and disease-related damage develop in a subgroup of patients, especially among those with ocular or vascular involvement. With the recent understanding of the immuno-pathogenesis, biologic treatments targeting potential pathogenic cells, cytokines or pathways are better optimized in BD. Data from large series showed that tumor necrosis factor-alpha inhibitors and interferon-alpha are effective and safe treatment options for the treatment of refractory and major organ involvement, such as ocular, neurologic, vascular, and gastrointestinal. Anakinra and ustekinumab also seem to be promising agents for refractory mucocutaneous disease. IL-1 inhibitors and tocilizumab may be alternatives for the treatment of patients with refractory eye involvement. Still, randomized controlled trials of biologic agents, especially for the treatment of major organ involvement, are insufficient, and further prospective, long-term follow-up studies are needed to clarify the efficacy, safety, and optimal treatment duration of biologic agents in BD.
Keywords: Behcet's disease; treatment; biologic agents; GENOME-WIDE ASSOCIATION; LONG-TERM EFFICACY; REFRACTORY NEURO-BEHCET; REGULATORY T-CELLS; MHC CLASS-I; INTERFERON-ALPHA; REMISSION INDUCTION; SEVERE UVEITIS; OPEN-LABEL; INFLIXIMAB TREATMENT